ANALISIS PENGARUH RISIKO KEUANGAN TERHADAP RETURN SAHAM PERBANKAN DI BURSA EFEK INDONESIA - Rizky Fara Safitri (2022)
This research aims to analyze financial risk, including liquidity risk, credit risk, and market risk on stock returns of banks listed on the Indonesia Stock Exchange for the period 2016 to 2020. The sample used in this study was 37 banking companies selected using the saturated sample method. The analytical technique used in this study is Panel Data Regression Analysis with Eviews program version 12 and a significance level of 5%. The results of this study indicate that (1) liquidity risk proxied by Loan to Deposit Ratio (LDR) has no effect on stock returns, (2) credit risk proxied by Non Performing Loans (NPL) has no effect on stock returns, and (3) market risk as proxied by stock beta had positive and significant effect on stock returns.